Self-collected biospecimen consent and return rates in a population-based study among women with ovarian cancer: insights from the ORCHiD study - April Deveaux; Drew Neish; Ashwini Joshi; Shenae Samuels; Oyomoare L. Osazuwa-Peters; Veronica Duck; Ashliegh Williams; Margaret Gates Kuliszewski; Bin Huang; Kevin Ward; Maria Pisu; Thomas Tucker; et al. (Cancer Causes & Control, 2026)

The effect of climate policies on firm financing and investment through the banking channel - Filippo Maria D'Arcangelo; Tobias Kruse; Mauro Pisu; Marco Tomasi (Journal of Environmental Management, 2025)

Effect of a subcutaneous implant of deslorelin acetate on serum testosterone concentrations in male Hermann’s (Testudo hermanni sp.) and Greek (Testudo graeca sp.) tortoises - Maria Carmela Pisu; Alice Andolfatto; Angelica Ferro; Simona Esposito; Maria Cristina Veronesi; Monica Probo (Veterinary Research Communications, 2023)

Therapeutic Use of Cerebellar Intermittent Theta Burst Stimulation (iTBS) in a Sardinian Family Affected by Spinocerebellar Ataxia 38 (SCA 38) - Angela Sanna; Paolo Follesa; Paolo Tacconi; Mariangela Serra; Maria Giuseppina Pisu; Viola Cocco; Michela Figorilli; Giovanni Defazio; Monica Puligheddu (The Cerebellum, 2022)
Spinocerebellar ataxia 38 (SCA 38) is an autosomal dominant disorder caused by conventional mutations in the ELOVL5 gene which encodes an enzyme involved in the synthesis of very long fatty acids, with a specific expression in cerebellar Purkinje cells. Three Italian families carrying the mutation, one of which is of Sardinian descent, have been identified and characterized. One session of cerebellar intermittent theta burst stimulation (iTBS) was applied to 6 affected members of the Sardinian family to probe motor cortex excitability measured by motor-evoked potentials (MEPs). Afterwards, patients were exposed to ten sessions of cerebellar real and sham iTBS in a cross-over study and clinical symptoms were evaluated before and after treatment by Modified International Cooperative Ataxia Rating Scale (MICARS). Moreover, serum BDNF levels were evaluated before and after real and sham cerebellar iTBS and the role of BDNF Val66Met polymorphism in influencing iTBS effect was explored. Present data show that one session of cerebellar iTBS was able to increase MEPs in all tested patients, suggesting an enhancement of the cerebello-thalamo-cortical pathway in SCA 38. MICARS scores were reduced after ten sessions of real cerebellar iTBS showing an improvement in clinical symptoms. Finally, although serum BDNF levels were not affected by cerebellar iTBS when considering all samples, segregating for genotype a difference was found between Val66Val and Val66Met carriers. These preliminary data suggest a potential therapeutic use of cerebellar iTBS in improving motor symptoms of SCA38.

Juvenile social isolation affects maternal care in rats: involvement of allopregnanolone - Maria Giuseppina Pisu; Giorgia Boero; Francesca Biggio; Anna Garau; Daniela Corda; Mauro Congiu; Alessandra Concas; Patrizia Porcu; Mariangela Serra (Psychopharmacology, 2017)

Changes in stress-stimulated allopregnanolone levels induced by neonatal estradiol treatment are associated with enhanced dopamine release in adult female rats: reversal by progesterone administration - Patrizia Porcu; Valeria Lallai; Andrea Locci; Sandro Catzeddu; Valeria Serra; Maria Giuseppina Pisu; Mariangela Serra; Laura Dazzi; Alessandra Concas (Psychopharmacology, 2017)

Allopregnanolone modulation of HPA axis function in the adult rat - Giovanni Biggio; Maria Giuseppina Pisu; Francesca Biggio; Mariangela Serra (Psychopharmacology, 2014)

Mammography utilization among Black and White Medicare beneficiaries in high breast cancer mortality US counties - Mandeep K. Virk-Baker; Michelle Y. Martin; Robert S. Levine; Xin Wang; Tim R. Nagy; Maria Pisu (Cancer Causes & Control, 2013)

Breast cancer screening interventions in selected counties across US regions - Shamly Austin; Michelle Y. Martin; Robert S. Levine; Maria Pisu (Cancer Causes & Control, 2010)

Immunocytochemical study of the forebrain serotonergic innervation in Sardinian alcohol-preferring rats - Maria Antonietta Casu; Carla Pisu; Carla Lobina; Luca Pani (Psychopharmacology, 2004)